CIVIL LIABILITY OF STATE-OWNED ENTERPRISE DIRECTORS FOR THE IMPLEMENTATION OF SPECIAL ASSIGNMENTS - Agustinus Nugroho Jati; Sri Gambir Melati Hatta; Gunawan Widjaja; Dyah Ersita Yustanti (INJOSEDU: International Journal of Social and Education, 2026)
This study examines the civil liability of Directors of State-Owned Enterprises (SOEs) when executing special assignments of the state under the reformed framework of Law SOE 2025. Research questions: (1) How should directors’ civil liability be assessed through the lens of the Company Law and the Business Judgment Rule (BJR)? (2) What are the proper form and limits of that liability when special assignments generate losses, and what regulatory model best aligns with Good Corporate Governance (GCG)? Method: doctrinal (normative) legal research using statute, conceptual, and case approaches; prescriptive qualitative analysis. Grand Theory: welfare state; Middle Range Theory: fiduciary duty and BJR; corporate governance (GCG/OECD-SOE) as the applied theory. Analysis shows that Law 1/2025 (i) ring-fences SOE property (Arts. 4A(5), 4B), (ii) codifies BJR for SOE organs (Art. 9F), and (iii) restructures special assignments (Arts. 87C–87D: presidential decree, separate accounting, and state funding if financially unviable). Through Art. 94A(b), asset/profit-loss status follows this law as lex specialis. The dissertation proposes a Two-Gate Test: Gate-1 (BJR-first) four cumulative BJR prongs; Gate-2 (Public-Money test) criminal law engages only when public funds (budget/equity injections/compensation/guarantees) are directly impaired and/or there is unlawful conduct (fraud/conflict of interest). Findings: (i) directors' civil liability is fault-based, not outcome-based; (ii) business loss ≠ state loss; (iii) a hybrid model (corporate layer and assignment layer) anchored in BJR and GCG is most proportionate; (iv) harmonisation of the State Finance Law with Law 1/2025 and BJR-first, Public-Money-second enforcement guidance is required to prevent over-criminalisation while safeguarding public accountability.